Pengembangan Buku Teks Tentang Macam-Macam Fi’il Terhadap Pengajaran Ilmu Nahwu - Lia Meilinda; Moch Mu'izzuddin; Siti Shalihah (Uktub: Journal of Arabic Studies, 2022)
Learning Arabic at Madrasah Tsanawiyah Masyariqul Anwar has various difficulties. 30 students who think Arabic is a scary thing, especially for novice students who are new to learning Arabic and the sources of teaching materials use Arabic without an intermediate language, especially nahwu. So the question is, how to develop a textbook on nahwu so that students can understand it as an interesting and easy to understand learning resource. The purpose of this study is to find out the real condition of teaching materials about various fi'il, to find out how to develop textbooks about various fi'il, to find out how far the effectiveness of developing the use of textbooks in various fi'il subjects is. and to find out the advantages and disadvantages of textbooks before and after being developed on various fi'il subjects for class VII MTs Masyariqul Anwar Pandeglang Banten towards the teaching of nahwu. The development theory used is Borg and Gall which contains ten steps but only six steps are used. The research tools used were observation, interviews and pre-test and post-test. All of the result can be seen after the application of nahwu textbooks in research which were tested with a post-test greater than the pre-test, namely: 76% greater than 53% In short, the development and application of textbooks on various fi'il have great effectiveness on learning nahwu students of class VII MTs Masyariqul Anwar Pandeglang Banten.